The learning curve: A neurosurgeon's memoir - Manjul Tripathi (Romanian Neurosurgery)
"The Learning Curve: A Neurosurgeon's Memoir," authored by Brigadier Harjinder Singh Bhatoe, is an autobiography of an Indian military neurosurgeon. The author invites readers on an intimate exploration of a life shaped by triumphs, tribulations, and the relentless pursuit of self-discovery as a soldier neurosurgeon. This autobiography is a poignant testament to the resilience of the human spirit and the transformative power of personal growth.